Global Transcriptome Analysis of Primary Cerebrocortical Cells: Identification of Genes Regulated by Triiodothyronine in Specific Cell Types. - Gil-Ibañez, Pilar; Garcia-Garcia, Francisco; Dopazo, Joaquin; Bernal, Juan; Morte, Beatriz (Cereb Cortex, 2017)
Thyroid hormones, thyroxine, and triiodothyronine (T3) are crucial for cerebral cortex development acting through regulation of gene expression. To define the transcriptional program under T3 regulation, we have performed RNA-Seq of T3-treated and untreated primary mouse cerebrocortical cells. The expression of 1145 genes or 7.7% of expressed genes was changed upon T3 addition, of which 371 responded to T3 in the presence of cycloheximide indicating direct transcriptional regulation. The results were compared with available transcriptomic datasets of defined cellular types. In this way, we could identify targets of T3 within genes enriched in astrocytes and neurons, in specific layers including the subplate, and in specific neurons such as prepronociceptin, cholecystokinin, or cortistatin neurons. The subplate and the prepronociceptin neurons appear as potentially major targets of T3 action. T3 upregulates mostly genes related to cell membrane events, such as G-protein signaling, neurotransmission, and ion transport and downregulates genes involved in nuclear events associated with the M phase of cell cycle, such as chromosome organization and segregation. Remarkably, the transcriptomic changes induced by T3 sustain the transition from fetal to adult patterns of gene expression. The results allow defining in molecular terms the elusive role of thyroid hormones on neocortical development.
Keywords: Animals; Astrocytes; Cells, Cultured; Cerebral Cortex; Fluorescent Antibody Technique; Gene Expression Profiling; Mice, 129 Strain; Mice, Inbred BALB C; Mice, Inbred C57BL; Neurons; Piperazines; Transcriptome; Triiodothyronine

Early transcriptional defense responses in Arabidopsis cell suspension culture under high-light conditions. - González-Pérez, Sergio; Gutiérrez, Jorge; Garcia-Garcia, Francisco; Osuna, Daniel; Dopazo, Joaquin; Lorenzo, Oscar; Revuelta, José L; Arellano, Juan B (Plant Physiol, 2011)
The early transcriptional defense responses and reactive oxygen species (ROS) production in Arabidopsis (Arabidopsis thaliana) cell suspension culture (ACSC), containing functional chloroplasts, were examined at high light (HL). The transcriptional analysis revealed that most of the ROS markers identified among the 449 transcripts with significant differential expression were transcripts specifically up-regulated by singlet oxygen ((1)O(2)). On the contrary, minimal correlation was established with transcripts specifically up-regulated by superoxide radical or hydrogen peroxide. The transcriptional analysis was supported by fluorescence microscopy experiments. The incubation of ACSC with the (1)O(2) sensor green reagent and 2',7'-dichlorofluorescein diacetate showed that the 30-min-HL-treated cultures emitted fluorescence that corresponded with the production of (1)O(2) but not of hydrogen peroxide. Furthermore, the in vivo photodamage of the D1 protein of photosystem II indicated that the photogeneration of (1)O(2) took place within the photosystem II reaction center. Functional enrichment analyses identified transcripts that are key components of the ROS signaling transduction pathway in plants as well as others encoding transcription factors that regulate both ROS scavenging and water deficit stress. A meta-analysis examining the transcriptional profiles of mutants and hormone treatments in Arabidopsis showed a high correlation between ACSC at HL and the fluorescent mutant family of Arabidopsis, a producer of (1)O(2) in plastids. Intriguingly, a high correlation was also observed with ABA deficient1 and more axillary growth4, two mutants with defects in the biosynthesis pathways of two key (apo)carotenoid-derived plant hormones (i.e. abscisic acid and strigolactones, respectively). ACSC has proven to be a valuable system for studying early transcriptional responses to HL stress.
Keywords: Arabidopsis; Blotting, Western; Cell Culture Techniques; Cells, Cultured; Chloroplasts; Cluster Analysis; Gene Expression Profiling; Gene Expression Regulation, Plant; Hydrogen Peroxide; Light; mutation; Oligonucleotide Array Sequence Analysis; Photosystem II Protein Complex; Plant Growth Regulators; Reproducibility of Results; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Signal Transduction; Stress, Physiological; Transcription, Genetic